Removing the hidden resources (de la) therapist: permitted improvise - Ulloa Hernández, Cynthia (2014)
In this paper, the concept of improvisation in psychotherapy is reviewed. The concepts of effective therapist (a) and improvisation are described, distinguishing the resources that influence both elements are linked, becoming in the psychotherapeutic success. 3 Creative methodologies therapeutic work are described. Literature from psychology and policy was reviewed and it was concluded that a (an) effective therapist improvising successfully establishes a positive link with the person and makes flexible use of psychological technique and their own knowledge based on the needs presents person served. Finally, some thoughts are raised to visualize the cross-influence exercise paradigm, gender and class in the therapeutic process.